Topical anaesthesia for needle‐related pain in newborn infants - Foster, Jann P (Cochrane Database Syst Rev, 2017)
BACKGROUND: Hospitalised newborn neonates frequently undergo painful invasive procedures that involve penetration of the skin and other tissues by a needle. One intervention that can be used prior to a needle insertion procedure is application of a topical local anaesthetic. OBJECTIVES: To evaluate the efficacy and safety of topical anaesthetics such as amethocaine and EMLA in newborn term or preterm infants requiring an invasive procedure involving puncture of skin and other tissues with a needle. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase and CINAHL up to 15 May 2016; previous reviews including cross‐references, abstracts, and conference proceedings. We contacted expert informants. We contacted authors directly to obtain additional data. We imposed no language restrictions. SELECTION CRITERIA: Randomised, quasi‐randomised controlled trials, and cluster and cross‐over randomised trials that compared the topical anaesthetics amethocaine and eutectic mixture of local anaesthetics (EMLA) in terms of anaesthetic efficacy and safety in newborn term or preterm infants requiring an invasive procedure involving puncture of skin and other tissues with a needle DATA COLLECTION AND ANALYSIS: From the reports of the clinical trials we extracted data regarding clinical outcomes including pain, number of infants with methaemoglobin level 5% and above, number of needle prick attempts prior to successful needle‐related procedure, crying, time taken to complete the procedure, episodes of apnoea, episodes of bradycardia, episodes of oxygen desaturation, neurodevelopmental disability and other adverse events. MAIN RESULTS: Eight small randomised controlled trials met the inclusion criteria (n = 506). These studies compared either EMLA and placebo or amethocaine and placebo. No studies compared EMLA and amethocaine. We were unable to meta‐analyse the outcome of pain due to differing outcome measures and methods of reporting. For EMLA, two individual studies reported a statistically significant reduction in pain compared to placebo during lumbar puncture and venepuncture. Three studies found no statistical difference between the groups during heel lancing. For amethocaine, three studies reported a statistically significant reduction in pain compared to placebo during venepuncture and one study reported a statistically significant reduction in pain compared to placebo during cannulation. One study reported no statistical difference between the two groups during intramuscular injection. One study reported no statistical difference between EMLA and the placebo group for successful venepuncture at first attempt. One study similarly reported no statistically significant difference between Amethocaine and the placebo group for successful cannulation at first attempt. Risk for local redness, swelling or blanching was significantly higher with EMLA (typical risk ratio (RR) 1.65, 95% confidence interval (CI) 1.24 to 2.19; typical risk difference (RD) 0.17, 95% CI 0.09 to 0.26; n = 272; number needed to treat for an additional harmful outcome (NNTH) 6, 95% CI 4 to 11; I(2) = 92% indicating considerable heterogeneity) although not for amethocaine (typical RR 2.11, 95% CI 0.72 to 6.16; typical RD 0.05, 95% CI ‐0.02 to 0.11, n = 221). These local skin reactions for EMLA and amethocaine were reported as short‐lasting. Two studies reported no methaemoglobinaemia with single application of EMLA. The quality of the evidence on outcomes assessed according to GRADE was low to moderate. AUTHORS' CONCLUSIONS: Overall, all the trials were small, and the effects of uncertain clinical significance. The evidence regarding the effectiveness or safety of the interventions studied is inadequate to support clinical recommendations. There has been no evaluation regarding any long‐term effects of topical anaesthetics in newborn infants. High quality studies evaluating the efficacy and safety of topical anaesthetics such as amethocaine and EMLA for needle‐related pain in newborn term or preterm infants are required. These studies should aim to determine efficacy of these topical anaesthetics and on homogenous groups of infants for gestational age. While there was no methaemoglobinaemia in the studies that reported methaemoglobin, the efficacy and safety of EMLA, especially in very preterm infants, and for repeated application, need to be further evaluated in future studies.